Cytoplasmic localization of SBR (Dm NXF1) protein and its zonal distribution in the ganglia of Drosophila melanogaster larvae. - Yakimova, A.O.; Pugacheva, O.M.; Golubkova, E.V.; Mamon, L.A. (Invertebrate Neuroscience, 2016)
The Drosophila gene Dm nxf1 (nuclear export factor 1) previously known as small bristles (sbr) controls nuclear export of various mRNA transcripts. We found that Dm NXF1 is present not only in nucleoplasm or at the nuclear rim but also in the cytoplasm. On the spatiotemporal level, anti-SBR antibodies labeled some neuroblasts and their lineages in the brains of Drosophila larvae. The number of Dm NXF1-rich lineages increased during larval development, but Dm NXF1 expression was not evident in all lineages. In all larval stages, Dm NXF1 concentrated in the midline cells of the ventral nerve cord, which reflects a specific status of those cells. In neurites, Dm NXF1 was present in the form of cytoplasmic granules, which is similar to the behavior of another RNA-binding protein, dFMR. Interestingly, though, the granule expression pattern of Dm NXF1 and dFMR did not always overlap, as some granules stained exclusively for one or the other protein. It suggests the existence of specific mRNA partners for Dm NXF1 in neurites.